2009
DOI: 10.1002/mds.22577
|View full text |Cite
|
Sign up to set email alerts
|

The syndromal validity and nosological position of apathy in Parkinson's disease

Abstract: Although apathy is among the most frequent behavioral changes in Parkinson's disease (PD), its diagnosis is still problematic, and the overlap with depression and dementia poorly studied. Aim of the study was validate specific criteria to diagnose apathy in PD, and to examine its association with subsyndromes of depression and dementia. A series of 164 patients with PD, 44 patients with "primary" depression and no PD, 23 patients with Alzheimer's disease, and 26 age-comparable healthy controls underwent a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 27 publications
(21 reference statements)
3
94
2
Order By: Relevance
“…A recent multicenter study of 1,072 consecutive patients conducted in Italy reported that apathy was associated with worse QOL, and that fatigue had a negative impact on QOL in PD (4). These findings further suggest that fatigue and apathy are strongly associated and overlap frequently (26,27). To date, the relationship between fatigue and apathy has not been investigated in detail.…”
Section: Discussionmentioning
confidence: 76%
“…A recent multicenter study of 1,072 consecutive patients conducted in Italy reported that apathy was associated with worse QOL, and that fatigue had a negative impact on QOL in PD (4). These findings further suggest that fatigue and apathy are strongly associated and overlap frequently (26,27). To date, the relationship between fatigue and apathy has not been investigated in detail.…”
Section: Discussionmentioning
confidence: 76%
“…Also within the domain of prefrontal executive functions more studies are needed: indeed most studies focused on functions of the orbital and of the dorsolateral frontostriatal circuits, while functions of the 'anterior cingulate' frontostriatal circuit (including the anterior cingulated cortex [ACC], the striatum [ventromedial caudate nucleus, ventral putamen] the nucleus accumbens, the olfactory tubercle, the globus pallidus [rostromedial] and the thalamus) have been scarcely investigated in PD: this circuit has been involved in motivated behavior, considering that its damages clinically result in apathetic syndromes [Bonelli and Cummings, 2007]. Apathy is a common neuropsychiatric feature also in PD patients [Starkstein et al 2009] and has been associated with cingulate anatomic reductions and functional deficits [Benoit and Robert, 2011;Kostic and Filippi, 2011] and with executive impairment [Poletti et al 2012a], but the role of nigrostriatal dopaminergic deficit on apathy in PD and the potential role played by dopaminergic drugs are actually almost unknown and deserve further empirical investigation.…”
Section: Future Directionsmentioning
confidence: 99%
“…They underwent a face-to-face interview and a clinical examination. They completed a standardised questionnaire including the following scales: ESS [9]; Horne-Ostberg morningness-eveningness scale [14]; Fatigue Severity Score [15,16]; Beck Depression Inventory II [17]; Hospital Anxiety and Depression Rating Scale [18]; Conners' Adult Attention Deficit-Hyperactivity Disorder Rating Scale [19]; and Apathy Scale [20]. The serum ferritin levels (as low levels promote restless legs and periodic leg movements [21]) and class II human leukocyte antigen (HLA) genotype (as the DQB1*0602 genotype is associated with sleepiness and narcolepsy) were determined.…”
Section: Investigationsmentioning
confidence: 99%